On a bending problem of thick laminated composite plates - Khoa, Ngo Nhu; Thinh, Ngo Ich (Vietnam Journal of Mechanics, 2002)
A high-order displacement field in quadrilateral element with nine nodes and twelve-degrees-of-freedom per node is developed for bending analysis of thick arbitrary layered composite plates under transverse loads. Results for plate deformations, internal stress-resultants and stresses for selected examples are shown to compare well with the closed-form and other finite element solutions.